Performance Evaluation and SWOT Analysis of Solar Powered Vapour Absorption Refrigeration System - Goswami, Nitin; Kumar, Jitender; Juneja, Deepak; Gupta, Amit (Journal of Advanced Research in Mechanical Engineering and Technology, 2021)
The solar cooling absorption system requires more research because of its poor COP. So, the study examined the performance of specific effect lithium bromide water (LiBr-H20) absorption system of cooling with 15 kW solar power. Space heating modes were also examined and improved methods were analyzed and discussed. The Vapor Absorption Machine (VAM) uses the LiBr-water solution to generate absorbent - refrigerant pair. The absorption system of cooling was operated by a trough collector of parabolic type of 36 sq m aperture are and 325 sq. feet was used to cool the meeting room. The results of the research show that For Parabolic Trough Collector maximum solar radiation was 954.86 W/m2 and the minimum solar radiation was 507.52 W/m2. The average COP of Parabolic Trough Collector was 0.46 and for absorption Refrigeration System the average COP calculated was 0.47. How to cite this article: Goswami N, Kumar J, Juneja D et al. Performance Evaluation and SWOT Analysis of Solar Powered Vapour Absorption Refrigeration System. J Adv Res Mech Engi Tech 2021; 8(2): 1-6.